DETEKSI SCHOOLING IKAN PELAGIS DENGAN METODE HIDROAKUSTIK DI PERAIRAN TELUK PALU, SULAWESI TENGAH - Achmadi, Andi; Hestirianoto, Totok; Manik, Henry M (Jurnal Teknologi Perikanan dan Kelautan, 2015)
Yield and catch data obtained from statistic and fisheries commercial data are incomplete and inaccurate. Effort to increase the accurate data and survey method become necessary to estimate the yield potential in Indonesia. The aim of this study was to detect the pelagic schooling (target strength/TS approach) by using hydroacoustic. Those detection were used to describe insitu condition of pelagic fishes in Palu Bay, Central Sulawesi. Result of this study on depth strata, dominant schooling (12 schools) found in 100 to 150 m, then followed by 9 schools in 0 to 50 m and 2 schools in 50 to 100 m. Fish caught in Palu Bay that landed in Labuan Bajo fishing port dominated by large pelagic. Those information were relevant with the TS data. The longest size of skipjack was 74 cm in depth of 142 m. Medium size of the smallest value of 5 cm was in depth 57 m with an average size of 27.80 cm.